The Interconnection of Huma Betang Values with the Philosophy of Pancasila in the Framework of Islamic Education at the Primary School Level at the Primary School Level - Harmini Harmini; Khairil Anwar (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2025)
Backround: Islamic education at the primary school level in Indonesia faces the challenge of integrating local cultural values with national ideology to build students’ character and social awareness. Aim: This study aimed to analyze the interconnection between Huma Betang values, rooted in Dayak culture, and the philosophy of Pancasila, and to explore how these values converge in the Islamic education curriculum to foster a generation with strong character and moderation. Method: Using a descriptive qualitative method, the research adopted an exploratory design with a systematic literature review. Relevant literature, including academic books, journal articles, and policy documents, was identified, selected based on defined criteria, and categorized into thematic groups. Data were analyzed through thematic analysis, enabling the identification, coding, and interpretation of recurring themes related to the integration of Huma Betang and Pancasila values in education. The findings revealed a significant convergence between Huma Betang principles—such as mutual cooperation, respect for diversity, and communal harmony—and the core values of Pancasila, including unity, humanity, and social justice. These values were embedded in the Islamic education curriculum through teaching materials, pedagogical strategies, and school activities like discussions, storytelling, and community-based learning. The integration of these values enriched the learning experience, cultivated social responsibility, and promoted tolerance among students, ultimately shaping individuals who are both academically competent and socially conscious. Despite the positive impacts, challenges remain, including limited resources, the need for teacher training, and translating philosophical concepts into practical curriculum implementation. Nonetheless, this integration holds considerable potential for strengthening national identity, preventing radicalization, and fostering an inclusive and harmonious society. Conclusion: the study underscores the importance of systematically incorporating both local and national values into Islamic education curricula at the primary school level to produce graduates with strong moral character and the capacity for social cohesion in a diverse society.